Randomised land use pathway generation allows efficient multi-outcome appraisal - Joshua P. Copping; Richard B. Bradbury; Rob H. Field; Tom Finch (Scientific Reports, 2025)
Abstract Land use scenario modelling with multi-criteria evaluation is an important tool for identifying integrated solutions to challenges such as biodiversity loss, climate change, and food production. Ideally, such models should identify efficient solutions from a large set of potential futures. Here, we generate 10,000 random future land use pathways for the UK, with each pathway deploying a randomly-drawn quantity of eight land-based climate change mitigation measures. We show that there are multiple paths to a net zero UK land sector, with wide-ranging impacts on food production and habitat availability for breeding birds. Whilst trade-offs are inherent, we identify pathways which are more efficient than a previous exercise which considered a more limited set of futures. We also explore the consequences of achieving efficiency at different spatial or governance scales, showing that whilst UK-scale decision-making is slightly more efficient, it results in less equitable outcomes than decision-making at devolved nation scales.